Folate-modified erythrocyte membrane nanoparticles loaded with Fe3O4 and artemisinin enhance ferroptosis of tumors by low-intensity focused ultrasound - Wang, Xingyue; Li, Peng; Jing, Xiangxiang; Zhou, Yun; Shao, Yongfu; Zheng, Min; Wang, Junrui; Ran, Haitao; Tang, Hailin (Frontiers in Oncology, 2022)
To overcome the challenges of the low efficiency of artemisinin (ART) in anticancer therapy due toits poor water solubility and poor bioavailability,we constructed folate (FA)-modifiederythrocyte membrane (EM)-camouflaged poly(lactic-co-glycolic acid)(PLGA) nanoparticles (NPs) (PFH/ART@PLGA/Fe3O4-eFA). Specifically, the inner core of these NPs is mainly composed of phase-changeable perfluorohexane(PFH), magnetic Fe3O4 and ART. In vitro experiments showed that the prepared PFH/ART@PLGA/Fe3O4-eFA was readily taken up by 4T1 cancer cells. PFH/ART@PLGA/Fe3O4-eFA was exposed to low-intensity focused ultrasound (LIFU) irradiation to induce PFH phase transition and NPs collapse, which promoted the release of ART and Fe3O4. After LIFU irradiation, the proportion of dead 4T1 cells, the level of reactive oxygen species (ROS) and the concentration of intracellular Fe2+ ions in the PFH/ART@PLGA/Fe3O4-eFA group were much higher than those inthe other group, indicating that the synergistic effect between the intracellular Fe2+ ions and the released ART played a critical role in tumor cell ferroptosis by enhancing ROS generation in vitro.We demonstrated that FA-modified EM NPs could enhance the targeting and accumulation of the NPs at the tumor site in vivo. After LIFU irradiation at 3 W/m2 for 7 min, tumor growth was completely suppressed through FA-modified EM NPs collapse and the release of ART and Fe3O4, which exerted synergistic effects in inducing tumor ferroptosis. Because of these characteristics, these NPs are considered as a promising approach for the delivery of drugs with poor water solubility for efficient cancer therapy.